Assessment of the Toxicity and the Stability of Saeng Mak San by Using Repeated Intravenous Injections in Sprague-Dawley Rats - Hwa-Young Lee; Sungchul Kim; Seung-Hun Cho (Korean Pharmacopuncture Institute, 2016)
Objectives: This study used repeated intravenous injections of Saeng Maek San (SMS) injection in Sprague-Dawley (SD) rats to assess the toxicity and the stability of SMS Methods: Six-week-old male and female SD rats reared by Orient bio Inc were chosen for this pilot study. They were randomly split into four groups: Group 1 (G1), the contr